BIOSYNTHESIS OF EXOPROTEASES BY BASIDIOMYCETES UPON SUBMERGED CULTIVATION (Proceedings of the YSU B: Chemical and Biological Sciences, 2003)
The possibility of biosynthesis of exoproteases by mushrooms Flammulina velutipes and Panus tigrinus is shown by means of selection of the appropriate nutrient medium, being the waste of a food- and agricultural industry. The tested nutrient medium, considering the addition of proper quantity of mineral components, provides optimum biosynthesis of proteases. Proteases and intracellular free amino acids, not involved in biosynthesis of proteases, are allocated in cultural liquid.
Keywords: exoproteases; mushrooms; food- and agricultural industry; nutrient medium